T-cadherin inhibits invasion and migration of endometrial stromal cells in endometriosis. Issue 1 (30th December 2019) - Lu, Qinsheng; Huang, Yanqing; Wu, Jiabao; Guan, Yutao; Du, Miaomiao; Wang, Fenghua; Liu, Zhihong; Zhu, Yali; Gong, Guifang; Hou, Huomei; Zhang, Min; Zhang, Joy Yue; et al.
Abstract: STUDY QUESTION: What is the expression level of T-cadherin in endometriosis, and does T-cadherin play a role in regulating invasion and migration of endometrial stromal cells? SUMMARY ANSWER: T-cadherin expression was reduced in ectopic endometriotic lesions compared to eutopic endometrium, and T-cadherin overexpression inhibited the invasion and migration of endometrial stromal cells. WHAT IS KNOWN ALREADY: Endometriosis is a disease that involves active cell invasion and migration. T-cadherin can inhibit cell invasion, migration and proliferation in various cancer cells, but its role in endometriosis has not been investigated. STUDY DESIGN, SIZE, DURATION: We explored the expression status of T-cadherin in 40 patients with and 24 without endometriosis. We also isolated endometrial stromal cells to study the invasion, migration and signaling pathway regulation of T-cadherin overexpression. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients were recruited at the Guangzhou Women and Children's Medical Center to study the expression levels of T-cadherin. The expression of T-cadherin was detected by immunohistochemistry staining and western blot. H-score was used to evaluate the staining intensity of T-cadherin. The correlation between T-cadherin expression levels (H-score) and endometriosis patients' age, stage, lesion size and adhesion was analyzed. Endometrial stromal cells from patients with and without endometriosis were isolated, and cell invasion and migration were detected by transwell assays after T-cadherin overexpression. The expression of vimentin in T-cadherin-overexpressed cells was detected by western blot. After T-cadherin overexpression, the phosphorylation profile of signaling pathway proteins was detected with the Proteome Profiler Human Phospho-Kinase Array Kit. MAIN RESULTS AND THE ROLE OF CHANCE: There was no difference in the expression of T-cadherin in the normal endometrium of control patients and the eutopic endometrium of endometriotic patients, but it was significantly decreased in the ectopic endometrium of endometriotic patients, compared with control endometrium and eutopic endometrium of endometriosis patients ( P  < 0.0001, for both). Western blot analysis also showed that the expression of T-cadherin was decreased in ectopic endometriotic lesions, but not the normal control endometrium or the endometriotic eutopic endometrium. The results of transwell assays indicated that T-cadherin overexpression inhibited the invasion and migration of endometrial stromal cells. In addition, T-cadherin overexpression promoted the phosphorylation of HSP27 (S78/S82) and JNK 1/2/3 (T183/Y185, T221/Y223) and decreased the expression of vimentin, MMP2 and MMP9 in eutopic endometriosis stromal cells. LARGE-SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: The control group were patients with benign gynecological conditions (e.g. uterus myoma, endometrial or cervical polyp), which may have genetic or epigenetic variations associated with T-cadherin expression and signaling pathways. The case numbers of involved endometriosis and control patients were limited. This study only used endometrial stromal cells from patients with or without endometriosis. Ideally, ectopic endometrial stromal cells of the ovarian endometriotic lesions should also be utilized to explore the function of T-cadherin. WIDER IMPLICATIONS OF THE FINDINGS: Further investigation of the role of T-cadherin in endometriosis may generate new potential therapeutic targets for this complex disorder. STUDY FUNDING AND COMPETING INTEREST(S): This study was supported by the Natural Science Foundation of Guangdong Province (2016A030313495), National Natural Science Foundation of China (81702567, 81671406, 31871412), the Science and Technology Programs of Guangdong (2017A050501021), Medical Science Technology Research Fund of Guangdong Province (A2018075), the Science and Technology Programs of Guangzhou City (201704030103), Internal Project of Family Planning Research Institute of Guangdong Province (S2018004), Post-doc initiation fund of Guangzhou (3302) and Post-doc science research initiation fund of Guangzhou Women and Children's Medical Center (20160322). There are no conflicts of interest.